A Study to Assess Preparedness of Dental Clinics for Medical Emergencies in Nepal - Mehta, Pawan; Singh, Amit Kumar; Yadav, Anil Kumar (Journal of Nobel Medical College, 2024)
Background: A medical emergency is an unwanted, unexpected reaction or complication. Effective management of an emergency situation in the dental office is ultimately the dentist responsibility. Materials and Methods: A descriptive study was carried out. Data were collected using a pre‑tested structured close‑ended self‑administered questionnaire. 465 general and/or specialist dental practitioner were selected from the registered member of Nepal Dental Association. Data entry and descriptive statistics analysis was done using Statistical package for social science version 26. Results: The results of the study show that the preparedness of dental clinics for medical emergencies was unsatisfactory. Only 47.1% of clinics have emergency kit and 33.8% have oxygen cylinder. Conclusion: The study shows that the dental clinics preparedness for medical emergency was not satisfactory and nearly half of the participants have knowledge on managing medical emergency at dental clinics.